Pediatric Sepsis by Multi-Drugs Resistance Organism: Length of Stay, Prognosis, and Hospitalization Cost Evaluation - Anindita Novia Damayanti; IGAA Putri Sri Rejeki; Ferdy Royland Marpaung (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Multi-Drugs Resistance (MDR) is a condition where bacteria are resistant to at least one type of antibiotic from three classes of antibiotics. One of the organisms included in the MDR is an Extended-Spectrum Beta Lactamase (ESBL) producing bacteria. Multi-drug resistance bacteria have been widely reported globally as a cause of severe infections. Still, information on the comparison of Length of Stay (LOS), hospitalization costs, and outcome status of the patients infected with MDR bacteria and infected with non-MDR bacteria is still limited. This study aimed to compare LOS, treatment costs, and outcome status of the BPJS pediatric sepsis patients infected with MDR bacteria and non-MDR bacteria in Dr. Soetomo General Academic Hospital, Surabaya. This study was observational research using medical records of hospitalized pediatric patients with BPJS insurance at the Dr. Soetomo General Academic Hospital from January 2015-July 2018 (n=49). The variables of this study were microbiology culture results and antibiotics sensitivity tests, LOS, INA-CBGs rates provided by BPJS, actual hospitalization cost, and outcome status. Statistical analyses were performed to compare LOS, INA-CBGs, actual cost, and outcome status of patients infected by MDR bacteria (ESBL and non-ESBL) or non-MDR bacteria. The results of this study include the average LOS value of non-MDR, MDR ESBL, and MDR non-ESBL cases, which were 30.55; 46.18; 32.41. Comparison of INA-CBGs and the actual cost of the three were 0.886 and 0.990, respectively, with p>0.05, and each percentage of the mortality patients was 27.3%, 45.5%, and 40.7%. There was no significant difference in the hospitalization cost and outcome status of patients infected by MDR bacteria (ESBL and non-ESBL) and non-MDR bacteria. Each percentage of LOS was also not much different. Still, MDR patients tended to be treated longer, require higher costs, and have a worseprognosis.